Experimental Study of Pulsed Discharge Underwater Shock-Related Properties in Pressurized Liquid Water - D. C. Bian; D. Yan; J. C. Zhao; S. Q. Niu (Advances in Materials Science and Engineering)
Engineering background of hydraulic fracturing is applied to improve the permeability of unconventional gas wells, such as coal seams and shale gas wells, by a pulsed discharge mechanism. We studied the general relations between water shock wave properties (the maximum pressure, wave velocity, and energy conversion efficiency), the discharge voltage, and hydrostatic pressure during high-voltage pulsed discharge experiments in pressurized liquid water. The following observations were made: (1) when the discharge voltage increased from 7 kV to 13 kV, the maximum pressure increased from 12.6 MPa (hydrostatic pressure PH = 12 MPa) to 40 MPa (PH = 6 MPa), wave velocity increased from 1418 m/s (PH = 12 MPa) to 1454 m/s (PH = 6 MPa), and energy conversion efficiency increased from 9% to 11%, and (2) when hydrostatic pressure increased from 0 MPa to 12 MPa, the maximum pressure and wave velocity augmented and then diminished slowly (the critical hydrostatic pressure occurs in the 3 to 6 MPa range), whereas the change of energy conversion efficiency was not obvious. Their properties are explained by the variation of electrical parameters during the pulsed discharge.